(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analytically examines the primary pedagogical and methodological challenges in developing clinical reasoning skills among medical students during cardiology teaching at higher education institutions. It discusses the context of Uzbekistan’s State Educational Standards (SES) for higher medical education and the professional standards for physician-cardiologists. Employing both quantitative (surveys, tests) and qualitative (interviews, focus groups) methods, the study identifies key impediments to students’ clinical reasoning formation—namely, theory-practice mismatch, insufficient practical base, and declining faculty qualifications. The article proposes targeted recommendations (curriculum enhancement, expanded use of simulation technologies, faculty development) to address these issues.